Electrochemical Analysis of Corrosion Resistance of Manganese-Coated Annealed Steel: Chronoamperometric and Voltammetric Study - Francisco Augusto Nuñez Pérez (AppliedChem)
Metal corrosion poses a significant challenge for industries by decreasing the lifespan of materials and escalating maintenance and replacement costs. This study is critically important, as it assesses the corrosion resistance properties of annealed steel wire electrodes coated with manganese, employing chronoamperometry and linear voltammetry techniques. The electrodes were immersed in an electrolyte solution and subjected to chronoamperometry at various voltages (−0.55 V, −0.60 V, and −0.70 V) and durations (60 s and 1800 s). Subsequently, linear voltammetry was performed over a potential range from −0.8 V to 0.8 V to generate Tafel plots. The Butler–Volmer equation was applied to the data obtained to determine the corrosion current density. The results indicate that the optimal conditions for forming a highly effective protective manganese layer occur at a potential of −0.70 V for 1800 s. Under these conditions, the electrodes exhibited superior corrosion resistance. This study also revealed that shorter durations and less negative potentials led to less-effective manganese coatings, with higher corrosion rates and reduced stability. These findings are significant for developing efficient corrosion protection methods in industrial and research applications, providing clear parameters for optimizing the manganese electrodeposition process on annealed steel.